La gravure sur bois - Rumpel, Heinrich (Genève : Les éditions De Bonvent, 1972)
Dürer, Albrecht ; Cranach, Lucas ; Holbein, Hans ; Rubens, Peter Paul ; Jegher, Christoffel ; Lievens, Jans ; Gauguin, Paul ; Munch, Edvard ; Kandinsky, Wassily ; etc.
Frans
boek
Keywords: Italië; Frankrijk; Duitsland; Japan